A Study on Ductility of Prestressed Concrete Pier Based on Response Surface Methodology - Wang, H.; Zhang, Y.; Qin, S. (Engineering, Technology & Applied Science Research, 2016)
The ductility of prestressed concrete pier is studied based on response surface methodology. Referring to the pervious prestressed concrete pier, based on Box-Behnken design, the ductility of 25 prestressed concrete piers is calculated by numerical method. The relationship between longitudinal reinforcement ratio, shear reinforcement ratio, prestressed tendon quantity, concrete compressive strength and ductility factor is gotten. The influence of the longitudinal reinforcement ratio, the shear reinforcement ratio, the prestressed tendon quantity and concrete compressive strength to curvature ductility is discussed. Then the ductility regression equation is deduced. The result showed that the influence of the prestressed tendon quantity to the ductility of prestressed concrete pier is significant. With the increasing of the prestressed tendon quantity, the curvature ductility curved reduces. With the increasing of shear reinforcement ratio and compressive strength of concrete, the curvature ductility increases linearly. And the influence of the longitudinal reinforcement ratio to ductility of the prestressed concrete pier is insignificant.